The correlation between IL-10 expression and histopathological type in nasopharynx carcinoma patients - Hamita Hamita; Muhtarum Yusuf; Manshur Shidiq Wiyadi (PERHATI-KL, 2020)
Background: Nasopharyngeal carcinoma (NPC) is a malignancy originated from nasopharyngeal epithelial cells. NPC therapy response could be predicted from histopathological type, but some patients with the same histopathological type, showed a different therapy response. Interleukin (IL)-10 expression is expected to be able to predict a better response of therapy in NPC patients. Purpose: To find out the correlation between IL-10 expression and histopathological type in NPC patients. Method: An analytic observational study with cross sectional approach towards 33 samples taken from the Oncology Polyclinic of Outpatient Unit of Otorhinolaryngology Head and Neck Surgery Department, Dr. Soetomo General Hospital. Formalin-fixed paraffin-embedded biopsy specimens were obtained. The IL-10 expression was studied with immunohistochemistry using rabbit polyclonal antibody Anti IL-10. Assessment of the staining used Allred scale. The Fisher exact test was utilized to determine the correlation of IL-10 expression and histopathological type of NPC, with p value = 0.05. Result: The result of IL-10 expression in NPC patients with histopathological WHO type I NPC obtained 1 sample (8.3%) with strong positive expression and 2 samples (9.5%) with weak positive expression. In patients with histopathological WHO type II NPC obtained 2 samples (16.7%) with strong positive expression and 12 samples (57.1%) with weak positive expression. In patients with histopathological WHO type III NPC obtained 9 samples (75%) with strong expression and 7 samples (33.3%) with weak positive expression. Conclusion: There was moderate positive correlation between IL-10 expression and histopathological type in NPC patients.Keywords: nasopharyngeal carcinoma, IL-10 expression, histopathological type ABSTRAK Latar belakang: Karsinoma nasofaring (KNF) adalah suatu keganasan yang berasal dari epitel nasofaring. Respon terapi KNF selama ini dapat dinilai berdasarkan tipe histopatologi, namun pada kenyataannya penderita KNF dengan tipe histopatologi sama dapat menunjukkan respon terapi berbeda. Pemeriksaan ekspresi interleukin (IL)-10 diharapkan dapat memberikan prediksi lebih baik mengenai respon terapi pada penderita KNF. Tujuan: Mengetahui hubungan antara ekspresi IL-10 dengan tipe histopatologi pada penderita KNF. Metode: Penelitian observasional analitik dengan pendekatan cross sectional pada 33 sampel yang diperoleh dari Poliklinik Onkologi Unit Rawat Jalan, Departemen THTBedah Kepala Leher, RSUD Dr Soetomo. Ekspresi IL-10 diperiksa dari blok parafin dengan teknik pemulasan imunohistokimia menggunakan rabbit polyclonal antibody Anti IL-10. Ekspresi IL-10 dinilai dengan menggunakan skala Allred. Uji Fisher exact digunakan untuk menentukan korelasi antara ekspresi IL-10 dan tipe histopatologi KNF, dengan p = 0,05. Hasil: Ekspresi IL-10 pada KNF WHO tipe I didapatkan ekspresi positif kuat 1 penderita (8,3%) dan ekspresi positif lemah 2 penderita (9,5%). Hasil ekspresi IL-10 pada KNF WHO tipe II didapatkan ekspresi positif kuat 2 penderita (16,7%) dan ekspresi positif lemah 12 penderita (57,1%). Hasil ekspresi IL-10 pada KNF WHO tipe III 9 penderita (75%) dengan ekspresi positif kuat dan 7 penderita (33,3%) dengan ekspresi positif lemah. Kesimpulan: Didapatkan korelasi positif sedang antara ekspresi IL-10 dan tipe histopatologi pada penderita KNF